A microRNA-129-5p/Rbfox crosstalk coordinates homeostatic downscaling of excitatory synapses - Rajman, Marek; Metge, Franziska; Dieterich, Christoph (The EMBO journal, 2017)
Synaptic downscaling is a homeostatic mechanism that allows neurons to reduce firing rates during chronically elevated network activity. Although synaptic downscaling is important in neural circuit development and epilepsy, the underlying mechanisms are poorly described. We performed small RNA profiling in picrotoxin (PTX)-treated hippocampal neurons, a model of synaptic downscaling. Thereby, we identified eight microRNAs (miRNAs) that were increased in response to PTX, including miR-129-5p, whose inhibition blocked synaptic downscaling in vitro and reduced epileptic seizure severity in vivo. Using transcriptome, proteome, and bioinformatic analysis, we identified the calcium pump Atp2b4 and doublecortin (Dcx) as miR-129-5p targets. Restoring Atp2b4 and Dcx expression was sufficient to prevent synaptic downscaling in PTX-treated neurons. Furthermore, we characterized a functional crosstalk between miR-129-5p and the RNA-binding protein (RBP) Rbfox1. In the absence of PTX, Rbfox1 promoted the expression of Atp2b4 and Dcx. Upon PTX treatment, Rbfox1 expression was downregulated by miR-129-5p, thereby allowing the repression of Atp2b4 and Dcx. We therefore identified a novel activity-dependent miRNA/RBP crosstalk during synaptic scaling, with potential implications for neural network homeostasis and epileptogenesis.
Gesehen am 28.11.2018